001 Melanocortin-4 Receptor Agonism Modulates Sexual Brain Processing in Women with Low Sexual Desire. (1st May 2022) - Hunjan, T.; Thurston, L.; Mills, E.; Wall, M.; Ertl, N.; Phylactou, M.; Muzi, B.; Patel, B.; Alexander, E.; Suladze, S.; Modi, M.; Eng, P.; et al.
ABSTRACT: Introduction: Hypoactive sexual desire disorder (HSDD) is characterized by a persistent lack of sexual desire and sexual fantasies, causing marked interpersonal distress 1 . It is the most common global female sexual health problem, affecting up to 1 in 10 women 2, 3 . Despite its significant social and economic burden 4, 5, the exact pathophysiology of this condition remains unknown. Furthermore, existing treatment options are limited by their efficacy and side effects 6 . Melanocortin-4 receptor (MC4R) agonists are a promising therapeutic avenue, although their exact mechanism of action within the CNS remains unknown. Investigating the neural pathways through which MC4Ra's exert their effect will deepen our knowledge of normal and abnormal sexual behaviour, and hence provide information which could contribute to the development of novel treatment strategies. Objective: To determine the mechanism by which MC4R agonists mediate their effects on sexual behaviour in women with HSDD. Methods: We performed a randomized, double-blind, placebo-controlled crossover study in 31 premenopausal women with HSDD. A combination of psychometric, functional neuroimaging and hormonal analyses was used to investigate the effect of MC4R agonism versus placebo on sexual brain processing. A standard fMRI block design task with short (20 second) erotic videos was used to examine brain activation. Additionally, a 'naturalistic' fMRI paradigm was used with long (ten minute) erotic videos to examine functional brain connectivity. Results: MC4R agonism increased self-reported sexual desire for up to 24-hours following administration, when compared with placebo (P=0.007). The mechanism of action behind this effect may be explained by the changes in brain activation and connectivity, in response to visual erotic stimuli. In the short video task, MC4R agonism led to increased activation of the supplementary motor area and cerebellum, alongside deactivation of the secondary somatosensory cortex, when compared with placebo (Z=2.3, P<0.05). In the long video task, a reduction of functional connectivity between the amygdala and insula in response to erotic stimuli was prevented by MC4R agonism (F (1, 30) = 5.553, P=0.025). Regarding hormonal analyses, MC4R agonism led to a small mean increase in LH of 1.1iU/L (F [1, 58] = 13.38, P=0.0005) and FSH of 0.35iU/L (F [1, 60] = 10.97, P=0.0016) during the study, with no effect on estradiol or progesterone levels. Conclusions: This is the first study investigating the effect of MC4R agonism on sexual brain processing in women with HSDD. These results shed light on the neural substrates through which MC4R agonism increases sexual desire. The observed changes in brain activation may serve to ease self-consciousness, enhance sexual imagery and disinhibit the sexual response in women with HSDD. This is in line with the "top-down" neurofunctional model of HSDD whereby inspecting and monitoring one's sexual response interferes with desire 7 . This information is important for the ongoing development of therapies for HSDD, as well as MC4R agonist development more widely, such as in obesity medicine where there their use is being rapidly developed. Disclosure: Work supported by industry: yes, by AMAG Pharmaceuticals Inc.